Kosmoscope: A Seismic Observatory - HAAHR, MADS; Redfern, Tim (ACM, 2009)
Earth tremors are a constant, intrinsic part of our planet's nature and a visceral experience when first encountered. Kosmoscope, a telematic art installation by Tim Redfern, marries two venerable technologies, the kaleidoscope and the seismograph, in order to immerse viewers within an abstract audiovisual representation of earth tremors. Kosmoscope uses state of the art seismic monitoring to render live scientific data impressionistically, making the worldwide network of ultra-sensitive seismic microphones audible and creating an imposing, visually fractured narrative that evokes the frailty of humanity in the face of geological forces. This paper describes the Kosmoscope's influences, aims, design and realisation.
Proceedings of the 17th ACM International Conference on Multimedia
Keywords: Earth tremors; Seismic observation; Seismic monitoring